Credit Decision Support System in Cooperative Fair - Ni Ketut Manika (Institute of Computer Science, 2020)
The credit distribution system in Cooperative Adil which is still manual, the many criteria used to consider and the number of members who make loans makes the cooperatives (especially managers) overwhelmed to serve their members and the granting process becomes less efficient. To overcome this problem, a Decision Support System for the provision of credit was built, namely a system that helps the cooperative (manager) in the process of granting credit. The system is built using the Delphi 7.0 programming language and the database uses mysql. The system built is used by two parties, namely administrators and managers. From the experimental results of the system that has been built, it can be concluded as follows: the system can provide convenience in obtaining information, the system becomes more selective in providing credit.